Simulation of typhoon-induced hydrodynamic conditions in the Hai Phong coastal area: a case study of Son Tinh typhoon 2012 and 2018 - Le Thi Thanh, Hue; Vinh, Vu Duy; Pham Tien, Dat (Vietnam Journal of Marine Science and Technology, 2024)
The Hai Phong coastal area is one of the places that is often affected by storms and tropical depressions, with significant impacts on hydrodynamics and geomorphological changes. The influence of typhoons on hydrodynamic conditions in the Hai Phong coastal area has yet to be thoroughly studied. Accordingly, the above study has evaluated the influence of storms with different trajectories on the hydrodynamic field in the Hai Phong coastal area under complex, non-linear impacts to contribute to a better understanding of the influence of storms on hydrodynamic processes and to improve research capacity on hydrodynamic regimes in coastal estuaries using modeling tools. Observational and reanalysis data from global sources were collected systematically and homogeneously to create open boundary conditions (time-serial) for the model. The NESTING method created sea boundary conditions for the model from another model with a larger grid outside. The Delft3D model system was set up with five vertical layers in Sigma coordinates and was validated, showing a fair agreement with measurement data at some places in the study area. Results of scenarios showed typhoons have an extreme impact on hydrodynamic conditions in the Hai Phong coastal area, especially raising the water level and increasing the flow velocity and wave height in the coastal area. Different typhoons effect the hydrodynamics differently, but they all share that the estuary areas with narrow channels are more strongly affected than the remaining areas. When the typhoons make landfall at the Lach Huyen estuary in Nam Trieu, the flow velocity can be up to 0.8–1.2 m/s (an increase of 0.5 m/s compared to the flow velocity in normal conditions), and the wave height can be up to 1.2–2.5 m (a rise of 0.4–2 m compared to the wave height in without typhoon).